Visible-Light-Activated Carbon Monoxide Release from Porphyrin-Flavonol Hybrids - Ramundo, Andrea; Janoš, Jiří; Muchová, Lucie; Šranková, Mária; Dostál, Jakub; Kloz, Miroslav; Vítek, Libor; Slavíček, Petr; Klán, Petr (Journal of the American Chemical Society, 2024)
We report on porphyrin-flavonol hybrids consisting of a porphyrin antenna and four covalently bound 3-hydroxyflavone (flavonol) groups, which act as highly efficient photoactivatable carbon monoxide (CO)-releasing molecules (photoCORMs). These bichromophoric systems enable activation of the UV-absorbing flavonol chromophore by visible light up to 650 nm and offer precise spatial and temporal control of CO administration. The physicochemical properties of the porphyrin antenna system can also be tuned by inserting a metal cation. Our computational study revealed that the process occurs via endergonic triplet-triplet energy transfer from porphyrin to flavonol and may become feasible thanks to flavonol energy stabilization upon intramolecular proton transfer. This mechanism was also indirectly supported by steady-state and transient absorption spectroscopy techniques. Additionally, the porphyrin-flavonol hybrids were found to be biologically benign. With four flavonol CO donors attached to a single porphyrin chromophore, high CO release yields, excellent uncaging cross sections, low toxicity, and CO therapeutic properties, these photoCORMs offer exceptional potential for their further development and future biological and medical applications.